2008
DOI: 10.1016/j.jnoncrysol.2008.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zirconium on the structure of pristine and leached soda-lime borosilicate glasses: Towards a quantitative approach by 17O MQMAS NMR

Abstract: a b s t r a c t 17 O MQMAS NMR was used to characterize the influence of zirconium on the structural organization of soda-lime borosilicate glasses. A new method of quantitative analysis of the 17 O MQMAS spectra is presented, by a direct fit of the two-dimensional MQMAS spectrum which provides the resolution of all the structural groups in glasses containing up to five oxides. Additional data were also obtained from the quantitative deconvolution of the 11 B MAS NMR spectra, with the help of the direct fit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 42 publications
6
72
0
Order By: Relevance
“…Galoisy et al (1999) and Angeli et al (2008) showed that Zr is 6-fold coordinated and conserves a similar local structural role in the gel. Angeli et al (2008) also observed that Ca remains in the gel as a Zr charge compensator. Ca, Sr, Si, Al, and Ba are also precipitated in the secondary phases, mainly in phyllosilicates and in phosphates for calcium .…”
Section: The Distribution Of Elements Between the Different Alteratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Galoisy et al (1999) and Angeli et al (2008) showed that Zr is 6-fold coordinated and conserves a similar local structural role in the gel. Angeli et al (2008) also observed that Ca remains in the gel as a Zr charge compensator. Ca, Sr, Si, Al, and Ba are also precipitated in the secondary phases, mainly in phyllosilicates and in phosphates for calcium .…”
Section: The Distribution Of Elements Between the Different Alteratiomentioning
confidence: 99%
“…Zr is mainly present in the gel layer due to its very low solubility (Arab et al, 2008). Galoisy et al (1999) and Angeli et al (2008) showed that Zr is 6-fold coordinated and conserves a similar local structural role in the gel. Angeli et al (2008) also observed that Ca remains in the gel as a Zr charge compensator.…”
Section: The Distribution Of Elements Between the Different Alteratiomentioning
confidence: 99%
See 1 more Smart Citation
“…For 1 D spectra typically 128 FIDs were accumulated for 29 Si and 11 B with a recycle delay of 16 and 2 s respectively. 11 B MQMAS experiments were performed using the RIACT-shifted echo pulse sequence [51 -53] with parameters given in Refs [54,55]. This pulse sequence was found to provide a much better sensitivity for observing boron-11 NMR signal in BO 3 units than the Z-filter pulse sequence.…”
Section: Dft and Gipaw Calculationsmentioning
confidence: 99%
“…Recent results suggest that the [ZrO 6 ] 2À groups are mainly compensated by calcium in the alteration layer [17]. We therefore decided to compensate the zirconium atoms preferentially by calcium atoms.…”
Section: Computer Glass Structurementioning
confidence: 99%